(untitled) (Archeomatica, 2021)
In the concluding speech of a 1992 symposium, "La conservation des monuments dans le bassin méditerranéen", J. Chamay said: "Je m’inquiète un peu de constater que vos recherches sont menées sans concertation organisée, chacun travaillant de son cà´té, l’échange d’information restant très limité . . . J’ai aussi le sentiment que la tendance générale parmi les chercheurs est de rester confiné dans sa spécialité . . . Attention à l’arbre qui cache la foràªt! Avant d’entrer dans le détail, une appréciation d’ensemble est nécessaire”. [I am a bit worried to note that you are carrying out your research without an organized dialogue, every person who works in his field, the exchange of information remains very limited. . . I also have the feeling that the general tendency of researchers is to remain confined to their own specialization. . . Beware of the tree that hides the forest! Before going into the details, an evaluation of the whole is needed.] Fortunately, more than 25 years have passed from the data of this consideration and for some time there has been full awareness among researchers that not only do we need to collaborate between conservation scientists belonging to different disciplines, but we must also draw on researchers who do not are involved in conservation. Some funding bodies are able to facilitate this collaboration and there is clear evidence of this in the programs managed by the EU for which research projects must be characterized by genuine collaboration between partners in more than one member state, with each partner providing a clearly defined contribution based on a particular experience. National standardization bodies such as UNI (Italian National Unification Body) in Italy and CEN (European Committee for Standardization) at European level, with the related Cultural Heritage sub-commission